Ni75Cu25O polyhedron material derived from nickel-copper oxalate as high-performance electrocatalyst for glucose oxidation. (January 2022) - Gu, Jiawei; Li, Qing; Zheng, Shasha; Kong, Qingquan; Xue, Huaiguo; Pang, Huan
Abstract: Nanomaterials are considered to possess considerable development potential in the field of electrocatalysis; however, these materials can be improved further as catalysts. We developed a polyhedral structure of Ni75 Cu25 O using calcining nickel-copper oxalate in air as an electrocatalyst for the glucose oxidation reaction (GOR). Compared with NiO obtained by calcining NiC2 O4 ·2H2 O directly under air-flow conditions, Ni75 Cu25 O obtained via Cu doping shows higher catalytic activity and sensitivity for glucose oxidation. Moreover, the synergy between Ni and Cu bimetals increases the number of active sites, and the rate of electrolyte diffusion, and electron transfer; thus, Ni75 Cu25 O has high sensitivity, high selectivity, high stability, and fast ampere response in the GOR. Graphical abstract: Image 1 Highlights: Doping Cu does not affect the original morphology of the material. There is a synergistic effect between Ni and Cu bimetals. Compared with NiO alone, Ni75 Cu25 O shows better stability and higher sensitivity.